Temporal dynamics of Th17 responses to Candida albicans in rheumatoid arthritis: Implications for immunity and treatment - Sri Handayani; Mustofa Mustofa (Romanian Journal of Rheumatology)
Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterized by symmetrical polyarthritis and systemic inflammation. Recent studies have highlighted the critical role of the Th17/IL-17 axis in RA pathogenesis, with elevated Th17 cell frequencies and IL-17 production contributing to disease progression. Candida albicans, a commensal fungus residing in mucocutaneous surfaces, relies on Th17-mediated immunity for protection against mucocutaneous candidiasis. However, RA patients exhibit impaired Th17 responses, increasing their susceptibility to C. albicans infections. This review examines the temporal dynamics of Th17 responses to C. albicans in RA patients, analyzing the expression trends of Th17 and regulatory T cells (Tregs) over 12, 24, and 48 hours. Findings indicate that RA patients have a diminished initial Th17 response, inadequate IL-17 production at peak activity, and sustained immune dysfunction, leading to compromised fungal clearance. Additionally, biologic therapies targeting the Th17/IL-17 pathway, while effective for RA symptom management, may exacerbate infection risks. Understanding these dynamics is crucial for developing strategies that enhance antifungal immunity without aggravating RA symptoms. Further research is essential to optimize treatment protocols that balance antifungal defenses and autoimmune regulation.